An Analytical Evaluation Of In Vitro Drug-Drug Interaction Studies For Fixed Artesunate Combination Therapy - Jayaraj, Vanessa Shalini Daniel (2010)
Drug-resistant Plasmodium falciparum has become a serious threat, especially in malaria-endemic regions of the world. In light of this, the WHO has recommended artemisinin combination therapy such as artesunate-mefloquine and artesunate-amodiaquine as first line treatment for uncomplicated falciparum malaria especially in regions harbouring the most resistant isolates. However, the in vitro drug interaction studies have not been conducted for both these combinations.